She Came from Kasaba. (October 2019) - Hakim-Dowek, Leslie
As in Marianne Hirsch's (2008) notion of 'devoir de memoire', this poem-piece, from a new series, uses the role of creation and imagination to strive to 're-activate and re-embody' distant family/historical transcultural spaces and memories within the perspective of a dispersed history of a Middle-Eastern minority, the Sephardi/Jewish community. There is little awareness that Sephardi/Jewish communities were an integral part of the Middle East and North Africa for many centuries before they were driven out of their homes in the second half of the twentieth century. Using a multi-modal approach combining photography and poetry, this photo-poem series has for focus my female lineage. This piece evokes in particular the memory of my grandmother, encapsulating many points in history where persecution and displacement occurred across many social, political and linguistic borders.